Knowledge and societal perceptions regarding autopsy amongst different educational backgrounds in Karachi, Pakistan - Marvi Masood Farooqui; Muhammad Ikram Ali; Qudsia Hassan; Rabbia Mahrukh; Nasibullah Ahmed (Journal of the Pakistan Medical Association, 2021)
Objective: The purpose of this study is to find out awareness levels about legislation/authorization and objectives of autopsy amongst the general public, in addition to their opinions about the topic based on the different levels of education. Methods: A cross-sectional questionnaire-based study design was implemented to collect data on their knowledge, perceptions and concerns regarding autopsy from a sample population of 260 citizens aged 18 and above from all educational backgrounds of District South Karachi, Pakistan. Results: Out of total respondents 47.1% (n=122) fell within the age range of 18-25. Males were 41.7% (n=106) and females were 56.3% (n=143) in the study. Out of the 82% (n=208) who marked “Yes” to knowing the meaning of autopsy, 55.3% (n=115) of the respondents belonged to high educational level, 44.7% (n=93) belonged to low educational level. Only 44.7% (n=93) participants correctly knew the purpose for conducting an autopsy. For concerns regarding autopsy a vast majority of respondents marked “Organ removal” (21.7%, n=135) and “Disfigurement of body” (18.3%, n=114) as the top two concerns across regardless of educational level. Conclusion: Although most people held positive perception of autopsy, in depth questioning revealed a clear lack of correct information amongst the general public regarding autopsies. This has led to many falsely held beliefs including fear of body disfigurement and organ removal and less faith in the medicolegal system, irrespective of educational background. Continuous....